The Role of Innovation in Mediating Organizational Learning and Personality towards Work Engagement In Indonesian SME’s - Winadi Prasetyoning Tyas, Ari Anggarani; Wahyuningsih, Dwi; Ummanah, Ummanah (Universitas Ibn Khladun Bogor, 2024)
The research aims to analyze organizational learning, personality through innovation on work engagement in small and medium enterprises in small industrial wholesalers in East Jakarta. The quantitative approach is used for employees of small and medium enterprises, small industrial wholesalers in East Jakarta Sample size using hair, rounding 200 respondent. Furthermore, the data were analyzed using the LISREL structural equation model. The results show that organizational learning does not have a direct effect on work engagement, but has an indirect effect on work engagement through innovation. Personality has a direct effect on Work Engagement but does not have an indirect effect through Innovation. The influence of personality on employee involvement to gain good awareness and responsibility. Furthermore, testing innovation as a mediator of the relationship between organizational learning and personality generates a new theory understand. The novelty in this study found that innovation greatly influences employee engagement because with a strong spirit has been formed as a result in shaping organizational learning and employee personality